Knowledge-based fault detection and isolation system for power plant simulator - Korbicz, Józef (1951- ); Uciński, Dariusz; Pieczyński, Andrzej (1953- ); Marczewska, Grażyna (Zielona Góra: Uniwersytet Zielonogórski)
A knowledge-based fault detection and isolation computer system for the power plant simulator in which the power boiler with 380t/h capacity collaborates with 125MW power turbine has been developed and implemented with the use of the expert system shell EXSYS.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka